Wilkinson power divider‐based cmos quasi‐circulator for single‐antenna radar systems. Issue 9 (27th June 2016) - Wang, Sen; Wu, Yen‐Bin
ABSTRACT: This letter presents lumped Wilkinson power divider (WPD)‐based quasi‐circulator (QC) for single‐antenna radar system applications at K‐band. The design incorporating a power amplifier (PA), a WPD, and a low‐noise amplifier (LNA), acts as a QC. All the circuits are designed and implemented in a standard 0.18‐μm CMOS process. The two amplifiers both adopt negative feedback to increase their circuit stability, and the PA uses a PMOS transistor for gate bias to improve its linearity. Moreover, the lumped WPD not only achieves compact size but also maintains excellent isolation and low loss. The overall performances can be also evaluated easily by the subcircuits. The proposed design features greater than 29.5‐dB isolation between TX and RX, and achieves 4.1‐dB and 7.8‐dB transmission gain from TX to ANT and ANT to RX, respectively. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2065–2068, 2016